An assessment of service users’ participation in community-based food and nutrition centres in the Northern Cape Province of South Africa - Boer, Olivia S.; Esau, Merlene C. (Social Work/Maatskaplike Werk, 2025)
A people-centred approach (PCA) advocates for community participation. Placing people at the centre of service delivery, this study evaluates community participation in the Northern Cape, focusing on individuals accessing services at community-based food and nutrition centres (CBFNCs). Adopting a quantitative research methodology, 14 CBFNCs were selected from a population of 143 centres. Of the approximately 33,000 beneficiaries from the 14 centres, 357 respondents were included. Data were collected through self-administered questionnaires and analysed by means of descriptive statistical analysis using the Statistical Package for the Social Sciences (SPSS). The study found that these centres are notably characterised by a lack of understanding of what a PCA entails and by low levels of participation as a result of centre-related and personal inhibiting factors that undermine participatory strategies. Recommendations include creating participation opportunities by involving beneficiaries in decision-making and inviting their input into policy-making, planning, implementation, budgeting, evaluation and analysis. Secondly, empowerment opportunities should be established to improve the knowledge of community members, improve their self-esteem, and enhance confidence and assertiveness as vital features of workable community programmes.